Satisfaction with perinatal care in women giving birth during the COVID-19 pandemic - Bejer, Agnieszka; Dziedzic, Agnieszka; Fedurko, Weronika; Frydrych, Angelika; Świst, Bernadetta; Schwartz, Marta; Majcher, Angelika; Inglot, Adrian (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. The role of a medical team during the perinatal period is significant, since it not only focuses on the patients’ physical health, but also impacts mental wellbeing. The aim of this study is to compare the level of satisfaction with the quality of care provided by healthcare professionals during pregnancy and perinatal period before and during the COVID-19 pandemic. Material and method. The study was conducted among 102 women who had at least two births, one in the pre-pandemic period and the other during the pandemic. An original questionnaire (53 items) was used to assess the quality of medical care. Results. The assessment of the quality of medical care, and the emotional and informational support received from medical personnel during pregnancy and perinatal care was significantly higher before the COVID-19 pandemic (p<0.001). During the pandemic, the respondents experienced significantly more anxiety about their health (p=0.027) and their baby’s health (p=0.028) as well as anxiety caused by the lack of a partner during labor (p<0.001). Conclusion. It is necessary to further evaluate the quality of medical care for pregnant and perinatal women in order to determine the best possible procedures for the functioning of health care in the time of a pandemic.
The study was approved by the Bioethics Committee of the College of Medical Sciences of the University of Rzeszow No. 2022/004. The authors have no conflict of interest. Additionally, there is no relationship of interest with any company in the study we are responsible for. No support was received from any project or company for the research.
Keywords: COVID-19 pandemic; pregnancy; quality of perinatal care